A trajetória educacional de alunos com deficiência, pela ótica familiar e de monitores da educação inclusiva em uma escola de ensino fundamental em Parintins-Am - Santos, Ana Paula Moraes dos (Brasil, 2023)
The present work aims to understand the educational trajectory of inclusion of three students with disabilities in the municipal public teaching network in the municipality of Parintins-AM, based on their life stories. From the family perspective, we will seek to analyze the importance of the family in the educational and social process of these subjects, and identify the importance of inclusive education through the reports of monitor teachers, as well as their challenges in the teaching-learning process of students with special educational needs. This research goes through the Life History method, based on the theoretical support in Glat (2009), Augras (2009), Ferrarotti (1993), among others. From the families' reports, it is possible to understand the daily struggles of those who have a person with a disability at home. teaches. It is emphasized in the reports of both investigated the importance of the school for the development and inclusion of the subject with disability. From this work, it is expected to contribute with a more humanized vision and with less stereotypes of students with disabilities, of the pseudo learning disability.